Single Mother Interpersonal Communications In Shaping Adolescent Children's Confidence (Descriptive Study In Jemirahan Village RT08/RW03 Jabon District, Sidoarjo): Komunikasi Interpersonal Single Mother Dalam Membentuk Kepercayaan Diri Anak Usia Remaja (Studi Deskriptif di Desa Jemirahan RT08/RW03 Kecamatan Jabon, Sidoarjo) - Berliana Bestari; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine and describe the interpersonal communication of single mothers in forming the self-confidence of adolescent children in Jemirahan Village RT08/RW03, Jabon District, Sidoarjo Regency. Data collection methods used in this study were observation and interviews. Observations were made in Jemirahan Village, RT 08/ RW 03, Jabon District, Sidoarjo Regency. Interviews were conducted with 4 (four) informants, namely JR (age 46 years), NH (age 36 years), JY (age 40 years) and NI (age 27 years). The data analysis used in this study consisted of three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study can be explained that there are 4 (four) general qualities of single mother success in forming children's self-confidence, namely 1) openness, 2) empathy, 3) supportiveness, and positive (positive) attitude. In addition, there are other aspects that can make a single mother able to form her child's self-confidence, namely accessibility.